Characterization of defect levels in β-Ga2O3 single crystals doped with tantalum. Issue 15 (31st March 2021) - Liu, Haoyue; Zhang, Naiji; Yin, Junhua; Xia, Changtai; Feng, Zhe Chuan; He, Kaiyan; Wan, Lingyu; Mohamed, H. F.
Abstract : Optical properties and defect characterization of Ta-doped β-Ga2 O3 single crystals grown by the optical floating zone method. Abstract : We present a detailed study on the crystal structure of 0.10 mol% Ta-doped β-Ga2 O3 crystals before and after annealing treatment in air by high-resolution X-ray diffraction and Raman spectroscopy, as well as the detection of point defects through the variation of photoluminescence excitation (PLE) and photoluminescence (PL) with temperature. Based on the experimental data, the band diagram of the 0.10 mol% Ta-doped β-Ga2 O3 crystal is constructed. The crystal quality of the 0.10 mol% Ta-doped β-Ga2 O3 crystal was improved after annealing treatment. The PL spectra exhibited two ultraviolet emission bands (UV ∼3.59 eV, UV′ ∼3.22 eV) and a blue emission band (BB ∼2.73 eV), which are ascribed to the recombination of self-trapped excitons at the trigonal OI and OII sites and gallium vacancies in the (2−) charge state (tetrahedral site), respectively. The work function of the 0.10 mol% Ta-doped β-Ga2 O3 crystal increased from 5.28 eV to 5.38 eV as a result of annealing treatment.